Do Profitability, Leverage, and Political Connections Affect Tax Avoidance? Evidence from Consumer Cyclical Sector Companies - Nur Fitriana Hamsyi; Apriyanti Apriyanti; Erni Panca Kurniasih; Metasari Kartika (Universitas Negeri Padang, 2023)
Purpose – This study empirically examines the effect of profitability, leverage, and political connections on tax avoidance.Design/methodology/approach – A total of 55 companies from the Consumer Cyclical sector on the Indonesia Stock Exchange were selected by purposive sampling. The analysis technique used is multiple linear regression analysis.Findings – The results show that profitability positively affects tax avoidance. By contrast, leverage and political connections did not affect the tax avoidance of consumer cyclical sector companies listed on the Indonesia Stock Exchange.Originality/value – The object of this research differs from that of previous studies, namely, consumer cyclical sector companies listed on the Indonesia Stock Exchange.Research limitations/implications – The limitation of this study is its relatively small sample size. The research implication is the role of the government or regulator in supervising and implementing effective tax rules to minimize tax avoidance practices.